2022
DOI: 10.1007/s12325-022-02118-0
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Symptoms, Health-Related Quality of Life, and Work Productivity in Japanese Women with Dysmenorrhea Receiving Different Treatments: Prospective Observational Study

Abstract: Introduction Dysmenorrhea is a physical and mental burden for women, negatively affecting health-related quality of life (HRQL) and work productivity. However, data on HRQL and work productivity of Japanese women are scarce. Methods In this prospective observational study, 397 Japanese women received low-dose estrogen/progestin (LEP) or non-LEP treatment (non-steroidal anti-inflammatory drugs or Chinese herbal medicines) for primary/secondary dysmenorrhea and completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 19 publications
0
16
2
Order By: Relevance
“…Menstrual symptoms, such as premenstrual syndrome (PMS), menstrual pain, and heavy menstrual bleeding, considerably lower women’s health-related quality of life [ 1 , 2 , 3 , 4 , 5 ]. PMS is described as either a poor psychological condition, such as irritability and anxiety, or physical discomfort, such as bloating, daytime drowsiness, and increased or decreased appetite, which typically lasts between 7 and 14 days before menstruation and disappears after it begins [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Menstrual symptoms, such as premenstrual syndrome (PMS), menstrual pain, and heavy menstrual bleeding, considerably lower women’s health-related quality of life [ 1 , 2 , 3 , 4 , 5 ]. PMS is described as either a poor psychological condition, such as irritability and anxiety, or physical discomfort, such as bloating, daytime drowsiness, and increased or decreased appetite, which typically lasts between 7 and 14 days before menstruation and disappears after it begins [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of menstrual symptoms on work performance, such as absenteeism (being absent from work), job performance, and productivity, has gained attention in business settings and its significance has been examined [ 4 , 8 , 9 , 10 , 11 , 12 ]. One study in the Netherlands found that 13.8% of 32,748 women reported absenteeism during their menstrual periods, with 3.4% reporting absenteeism every or almost every menstrual cycle [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that pain can be so disabling as to even affect performance of the activities of daily living [8]. Along with menstrual pain, it is usual for women to experience other menstrual symptoms that can affect their productive performance, with the consequent need to assess the impact of menstruation on work [9]. The data indicated that more than one-fourth of the women reduced their working hours or failed to attend work at least 1 day in the last 6 months due to painful menses [9].…”
Section: Introductionmentioning
confidence: 99%
“…Along with menstrual pain, it is usual for women to experience other menstrual symptoms that can affect their productive performance, with the consequent need to assess the impact of menstruation on work [9]. The data indicated that more than one-fourth of the women reduced their working hours or failed to attend work at least 1 day in the last 6 months due to painful menses [9]. This points to the fact that dysmenorrhea may not only be considered a health problem but also a social one, as it exerts an in uence on health-related quality of life [10].…”
Section: Introductionmentioning
confidence: 99%
“…Women with dysmenorrhea are vulnerable to have higher levels of depression, anxiety, negative selfperception and hostility [12]. Dysmenorrheic women are also prone to reduce productivity, creativity and job performance [13]. Among these complications, depressive disorder is one of the most commonly reported issue in women with dysmenorrhea.…”
Section: Introductionmentioning
confidence: 99%